2022
DOI: 10.1002/jmv.27817
|View full text |Cite
|
Sign up to set email alerts
|

Influenza is more severe than our newest enemy (COVID‐19) in hospitalized children: Experience from a tertiary center

Abstract: Background Understanding differences in terms of clinical phenotypes and outcomes of COVID‐19 compared with influenza is vital to optimize the management of patients and to plan healthcare.Herein,we aimed to investigate the clinical differences and outcomes in hospitalized patients with SARS‐CoV‐2 and influenza. Methods We performed a retrospective study of hospitalized children who were positive for SARS‐CoV‐2 between March 2020 and March 2021 and for influenza between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…13 Similar to our study, studies comparing hemogram parameters of patients with COVID-19-like symptoms and patients with COVID-19 reported lower leukocytes, neutrophils, and eosinophil counts in the COVID-19 group. [7][8][9]17 Although the virus is expected to cause lymphopenia due to damage to T-lymphocytes, there are conflicting results regarding lymphocyte counts in the literature. 8,9,18 Nonetheless, when patients with COVID-19 were compared with patients with COVID-19-like symptoms, it was shown that only lymphopenia could significantly distinguish patients in the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Similar to our study, studies comparing hemogram parameters of patients with COVID-19-like symptoms and patients with COVID-19 reported lower leukocytes, neutrophils, and eosinophil counts in the COVID-19 group. [7][8][9]17 Although the virus is expected to cause lymphopenia due to damage to T-lymphocytes, there are conflicting results regarding lymphocyte counts in the literature. 8,9,18 Nonetheless, when patients with COVID-19 were compared with patients with COVID-19-like symptoms, it was shown that only lymphopenia could significantly distinguish patients in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…6 In studies comparing COVID-19 and other viral infections in children, it has been reported that the lymphocyte count is lower in those with influenza infection, and the leukocyte and neutrophil counts are higher in patients with influenza and human adenovirus infections. [7][8][9] In studies comparing viral infections such as influenza and respiratory syncytial virus with COVID-19, the NLR was found to be lower in COVID-19. 8,10 Therefore, complete blood count parameters, which are frequently requested laboratory tests in the emergency department, can be used for diagnosis, especially in cases where serological or molecular tests cannot be performed rapidly in centers with limited resources or when demand exceeds supply due to seasonally increasing respiratory tract infections, and may be necessary for the isolation decision.…”
Section: Introductionmentioning
confidence: 99%
“…Although it was thought that our newest enemy (COVID-19) would cause more serious consequences than other respiratory tract infections, recent studies have revealed that influenza is not such a benign virus in children [ 25 ]. Tasar et al demonstrated that influenza caused more frequent admissions to intensive care units and a greater need for respiratory support in hospitalized pediatric patients than did COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This will allow doctors to implement appropriate treatment as soon as possible to make it as effective as possible. Based on the study by Tasar et al, it can be concluded that influenza can be a serious and frequent cause of complications in children [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte decrease or lymphopenia in children with influenza A or B and its association with disease severity have been reported. [28][29][30][31][32] Lymphopenia negatively affects the host adaptive immune responses and prolongs the clinical course of viral infection. 31 A recent study showed that CD4 + T cells promoted influenza virus-specific CD8 + T cell memory, and induced the differentiation of CD8 + cells into cytotoxic effector cells, which helped to eliminate virus.…”
mentioning
confidence: 99%